2015
DOI: 10.1007/s10980-015-0280-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of biotic resistance to invasions in forests of the Eastern USA

Abstract: Context Detecting biotic resistance to biological invasions across large geographic areas may require acknowledging multiple metrics of niche usage and potential spatial heterogeneity in associations between invasive and native species diversity and dominance.Objectives Determine (1) if native communities are resistant to biological invasions at macroscales; (2) the metrics that best quantify biotic resistance at these scales; and (3) the degree to which the direction and magnitude of invader-native associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 64 publications
(94 reference statements)
2
48
0
Order By: Relevance
“…While coarse deer density estimates such as those contained in the QDMA (2009) report may provide useful indicators of trends in deer herbivory as noted here, careful attention should be paid to the years in which deer density estimates are used to compare with forest understory measurements. Within the FIA program, a subset of invasive plant species are monitored across P2 plots which could be linked to biological resistance with a suite of forest attributes across regional scales (e.g., Oswalt et al, 2015;Iannone et al, 2016). Currently, FIA field crews are directly recording deer browse severity as a part of a new regeneration indicator (McWilliams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While coarse deer density estimates such as those contained in the QDMA (2009) report may provide useful indicators of trends in deer herbivory as noted here, careful attention should be paid to the years in which deer density estimates are used to compare with forest understory measurements. Within the FIA program, a subset of invasive plant species are monitored across P2 plots which could be linked to biological resistance with a suite of forest attributes across regional scales (e.g., Oswalt et al, 2015;Iannone et al, 2016). Currently, FIA field crews are directly recording deer browse severity as a part of a new regeneration indicator (McWilliams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…), invasion resistance (Iannone et al. ), and nutrient acquisition and cycling (Zeugin et al. ), among other processes.…”
Section: Methodsmentioning
confidence: 99%
“…Functional and phylogenetic clustering or overdispersion is often used to infer community assembly and, in some cases, community resistance to invasions (e.g., Iannone et al. ). In our analysis, functional and phylogenetic diversity per se played a more important role in shaping alien diversity patterns, while clustering or overdispersion had little to no added value in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Iannone et al. () showed that increased phylogenetic clustering limits alien species dominance and establishment.…”
Section: Introductionmentioning
confidence: 99%